Teacher Pedagogical Practices and Students’ Experiences in Narrative Text Writing Using Canva: A Case Study at Ma Miftahul Ulum Bettet - Kamilatul Unsa Unsa; Rini Listiyowati; Linta Wafdan Hidayah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to examine teachers’ pedagogical practices in teaching narrative writing using Canva and to explore students’ learning experiences in the classroom. This study employs a qualitative approach with a case study design conducted at MA Miftahul Ulum Bettet. Data were collected through classroom observations and semi-structured interviews involving one English teacher and 30 students. Observations were conducted to identify the stages of pedagogical practices implemented during the learning process, while interviews were conducted to gain a deeper understanding of students’ learning experiences. Data were analyzed using thematic analysis to identify patterns and main themes related to pedagogical practices and student engagement. The results indicate that the teacher implemented various pedagogical practices, such as introductory activities, modelling, collaborative learning, scaffolding, independent writing, and providing feedback, reflecting interactive and student-cantered learning. Furthermore, the use of Canva enhances student engagement, creativity, and the ability to organize ideas when writing narrative texts. This study contributes to the development of pedagogical practices in EFL instruction by emphasizing the importance of technology integration to create more effective and meaningful learning.